2017
DOI: 10.1016/j.aninu.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bacillus subtilis on growth performance, nutrition metabolism and intestinal microflora of 1 to 42 d broiler chickens

Abstract: To study the influence of different levels of Bacillus subtilis on growth performance, nutrition metabolism and intestinal microflora of 1 to 42 d Arbor Acres (AA) broilers, a total of 800 one-day-old healthy broilers were randomly divided into 5 groups with 4 replicates per group and 40 broilers per replicate. Broilers were fed a basic diet (group 1) which acted as the control group, and 4 other groups (2 to 5) were fed the basal diet with B. subtilis added at concentrations of 100, 150, 200 and 250 mg/kg, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 13 publications
6
53
0
3
Order By: Relevance
“…Choonkham and Suriyasathaporn (2018) reported that periparturient cows fed diets supplemented with B. subtilis at 0.5 × 10 11 CFU/day had lower risk of oxidative stress during the transition period under tropical conditions a factor related to the reduced milk production in heat-stressed cows (Guo et al, 2018). In poultry, supplementing B. subtilis under heat stress conditions improved the productive performance of broiler chickens (Gao et al, 2017;Wang et al, 2018) and laying hens (Fathi et al, 2018). Although, most of erythrocyte parameters and glucose decreased linearly as B. subtilis supplementation increased during the first period of the study, haematological and biochemical parameters in our study did not differ among treatments, and also were in line with the reference intervals established in the Animal Health Diagnostic Centre, College of Veterinary Medicine, Cornell University (Cornell University College of Veterinary Medicine, n.d.).…”
Section: Discussionmentioning
confidence: 99%
“…Choonkham and Suriyasathaporn (2018) reported that periparturient cows fed diets supplemented with B. subtilis at 0.5 × 10 11 CFU/day had lower risk of oxidative stress during the transition period under tropical conditions a factor related to the reduced milk production in heat-stressed cows (Guo et al, 2018). In poultry, supplementing B. subtilis under heat stress conditions improved the productive performance of broiler chickens (Gao et al, 2017;Wang et al, 2018) and laying hens (Fathi et al, 2018). Although, most of erythrocyte parameters and glucose decreased linearly as B. subtilis supplementation increased during the first period of the study, haematological and biochemical parameters in our study did not differ among treatments, and also were in line with the reference intervals established in the Animal Health Diagnostic Centre, College of Veterinary Medicine, Cornell University (Cornell University College of Veterinary Medicine, n.d.).…”
Section: Discussionmentioning
confidence: 99%
“…B. subtilis has been reported to inhibit the growth of pathogenic Gram-negative bacteria in poultry feeding [42,43]. In this study, both B. subtilis 87Y or L. lactis strains inhibited S. enteritidis and S. typhimurium (Fig.…”
Section: B Subtilis 87y Inhibits S Aureus Growth Through Su Productionmentioning
confidence: 56%
“…These results suggested that the short-term simultaneous addition (0~3 weeks) of AGP + B. subtilis seemed to be comparable with the long-term use of AGP for the maintenance of growth performance of 0~16 week-old pullets. Meanwhile, numerous studies from the past have shown that B. subtilis in various concentrations could promote the growth performance of chickens (Jeong and Kim, 2014 ; Li et al, 2015 ; Bai et al, 2017 ; Gadde et al, 2017 ; Gao et al, 2017 ; Jayaraman et al, 2017 ) when compared with the blank control group. In addition, Gadde et al ( 2017 ) showed that dietary co-supplementation of antibiotic and probiotics ( B. subtilis ) could significantly improve the feed efficiency as evidenced by decreased FCR compared with controls, but, also, there were no differences between AGP and probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in demand for poultry products with high quality, it is imperative to exploit effective special additives and related additive approach that can both stimulate the productive potential and maintain the health of broilers in order to gradually replace the AGPs (Yang et al, 2009 ; Bai et al, 2017 ). One such potential alternative of AGPs in poultry was Bacillus subtilis ( B. subtilis ), which could rebalance the intestinal microflora by creating an anaerobic environment and by competitively inhibiting the pathogen, improve growth performance by promoting intestinal development and by promoting the digestion and absorption functions, and enhance intestinal health by improving immune function (Guo et al, 2016 ; Gao et al, 2017 ; Jayaraman et al, 2017 ; Mahmouda et al, 2017 ). However, antibiotics can be withdrawn, but animals become more prone to infection, and it has negative effects on production yields (Gadde et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%